Interim Election as a Transitional Electoral Design in Indonesia - Devi Yulida; Rini Anggreini (Acta Law Journal, 2025)
The General Election serves as the primary means for citizens to carry out their sovereignty within Indonesias democratic framework. The Constitutional Court Decision Number 135/PUU-XXII/2024 introduced a major transformation by separating the National Election from the Regional Election, which had previously been conducted simultaneously. This separation aims to improve the quality of democracy and enhance electoral efficiency but simultaneously presents new challenges, notably the potential vacancy of Regional Representatives (DPRD) and regional heads during the 2029–2031 transition period due to differing electoral cycles. This study employs a normative juridical method with legislative and conceptual approaches to analyze the legal implications of the Court’s decision and to propose a constitutional solution through the concept of an Interim Election. The findings indicate that the Interim Election offers a legitimate and democratic mechanism to preserve the authority of representative institutions without extending their terms unconstitutionally. It applies only to DPRD members at the provincial and local levels, while regional head vacancies may be filled by acting officials in accordance with existing regulations. Therefore, the Interim Election provides a constitutional pathway to maintain governmental continuity, uphold the principle of periodic power limitation, and reinforce popular sovereignty in the aftermath of Constitutional Court Decision Number 135/PUU-XXII/2024.